Characterization of diarrheagenic Escherichia coli strains associated with diarrhea in children, Khouzestan, Iran - Sanaz Mahdavi Broujerdi; Mohammad Roayaei Ardakani; Seyedeh Elham Rezatofighi (Journal of Infection in Developing Countries)
Introduction: Diarrheagenic Escherichia coli (DEC) is a major etiologic agent among the pathogens that cause diarrhea in children.